The Effect of Chlordiazepoxide Consumption on the Hippocampus of Neonatal Rats During Pregnancy: - Hashemi, Mehrdad; Dinarvand, Amin; Dinarvand, Rasoul; Movassaghi, Shabnam; Jafarinia, Mojtaba (Galen Medical Journal, 2022)
Background: Chlordiazepoxide is an anti-anxiety drug commonly used by young people and pregnant women to reduce anxiety. The adverse effects of this drug on cholinergic nervous system function have been demonstrated. Therefore, in this study, the effect of chlordiazepoxide consumption during pregnancy was evaluated on the rats infant hippocampus. Materials and Methods: Nine pregnant Wistar rats were randomly divided (n=3 per group) into control, experimental (daily intraperitoneal injection of chlordiazepoxide at a dose of 10 mg/kg for 21 days), and vehicle (same amount of normal saline) groups. Two weeks after birth, the neonate brains were removed from the skull and prepared for Nissl and TUNEL stainings. The expressions of pro- and anti-apoptotic genes were evaluated. Results: The number of healthy neurons in different areas of the neonatal hippocampus in the experimental group was significantly reduced compared to control and vehicle groups, and the number of apoptotic bodies was increased (P<0.05). However, there was no significant difference between the numbers of these cells in the control and vehicle groups. The expression of pro-apoptotic genes in the experimental group increased significantly compared to the control group instead of the expression of anti-apoptotic genes decreased significantly. Conclusion: Chlordiazepoxide during pregnancy can cause neuronal damage in the hippocampus of neonatal Wistar rats.